Pengaruh Faktor Modal, Tenaga Kerja, Jam Kerja, dan Lama Usaha terhadap Pendapatan Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Alalak Utara, Kota Banjarmasin Selama Pandemi Covid-19 - Nugroho, Achmad Dwi; Siregar, Syahrituah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This research aims to understand whether the variables of capital, labor, working hours, and business duration have simultaneous and partial effects on the income of Micro, Small, and Medium Enterprises (UMKM) in Kelurahan Alalak Utara, Banjarmasin during the Covid-19 pandemic and identify the dominant factors influencing the income of UMKM in Kelurahan Alalak Utara, Banjarmasin during the Covid-19 pandemic. The study employs multiple linear regression analysis with capital (X1), labor (X2), working hours (X3), and business duration (X4) as independent variables against UMKM income during the Covid-19 pandemic (Y). The research findings indicate that collectively, capital, labor, working hours, and business tenure have a significant positive impact on UMKM income, supported by a significant F-test value. Partially, capital and business tenure have significant influence, while labor and working hours do not significantly affect it. Business capital proves to be the most dominant variable contributing to UMKM income during the pandemic.